2006
DOI: 10.1111/j.1600-0404.2005.00558.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of repetitive transcranial magnetic stimulation on voice and speech in Parkinson's disease

Abstract: Our findings provide initial evidence that rTMS of the primary motor cortex might yield a beneficial effect on vocal function in PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
1
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 33 publications
2
45
1
2
Order By: Relevance
“…To do so, we considered diseases in which a specific brain-stimulation site had been reported to be ineffective. For example, multiple randomized, controlled trials in Parkinson's disease have found that noninvasive stimulation to the left DLPFC fails to show significant motor improvements similar to those seen with noninvasive stimulation to M1 (48)(49)(50)(51)(52). Consistent with these findings, the Parkinson's DBS site in the subthalamic nucleus (STN) showed strong connectivity to M1 but not to the left DLPFC (Fig.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…To do so, we considered diseases in which a specific brain-stimulation site had been reported to be ineffective. For example, multiple randomized, controlled trials in Parkinson's disease have found that noninvasive stimulation to the left DLPFC fails to show significant motor improvements similar to those seen with noninvasive stimulation to M1 (48)(49)(50)(51)(52). Consistent with these findings, the Parkinson's DBS site in the subthalamic nucleus (STN) showed strong connectivity to M1 but not to the left DLPFC (Fig.…”
Section: Resultssupporting
confidence: 68%
“…5A). Excitatory stimulation to M1 results in an improvement in Parkinson's scores (50,(63)(64)(65)(66), but inhibitory stimulation shows little effect (63,64,67). In contrast, inhibitory stimulation to the SMA appears to improve scores (23,68,69), but excitatory stimulation leads to no effect or even to a worsening of symptoms (23,68,70).…”
Section: Resultsmentioning
confidence: 92%
“…Sua produção se faz através do movimento coordenado uniformidade e deslocamento dos formantes, aumento de jitter e das pausas articulatórias 1,[4][5][6] . Dentre as patologias associadas à senescência, destaca-se a Doença de Parkinson (DP), cuja estimativa está em torno de 40 milhões de pessoas no mundo com diagnóstico de DP em 2020 7 crescente. Contudo, no Brasil, não existem estimativas oficiais.…”
Section: Introductionunclassified
“…rTMS treatment in PD generally aims at improving motor symptoms, such as LIDs, bradykinesias and freezing of gait (FOG), though some studies also focused on non-motor symptoms, including depression and apathy [21], speech and voice [22,23] and cognitive functions [24].…”
Section: Rtms Rationale In Parkinson's Diseasementioning
confidence: 99%